Extracellular vesicles from different regions of the female reproductive tract promote spermatozoa motility and support capacitation - Camilla Fasoli; Elisa Giacomini; Valentina Pavone; Lisett Solano Narduche; Viviana Bonzi; Laura Privitera; Paolo Giardina; Ludovica Bartiromo; Matteo Schimberni; Luca Pagliardini; Enrico Papaleo; Massimo Candiani; et al. (Scientific Reports)
Abstract Extracellular vesicles (EVs) have been proven to have a crucial role in intercellular communication and have attracted significant attention in the physiology of reproduction because of their multiple functions in physiological processes essential for reproduction including gametogenesis, fertilization and embryo-endometrial cross-talk. Although EVs from the male reproductive tract have been extensively studied for their role in sperm maturation, research on female reproductive tract-derived EVs in humans is still emerging and supported by only a few studies to date. In vitro study was performed using spermatozoa from normozoospermic men and EVs isolated from follicular fluid (FF-EVs), cervicovaginal fluid collected 2 and 7 days after the LH surge (CVF-EVs LH + 2 and LH + 7, respectively) and spent medium of decidualized (dESCs-EVs) and non-decidualized (eESCs-EVs) endometrial stromal cells from healthy women of reproductive age. The principal outcome measures comprise the percentage of viable, progressively motile, and capacitated spermatozoa after treatment with FF-EVs, CVF-EVs LH + 2 and LH + 7, dESCs-EVs, and eESCs-EVs. Spermatozoa are able to capture EVs derived from all the considered tracts of the female reproductive system, with slightly varying efficiencies, albeit comparable in most cases. Incubating sperm cells with any of these EVs does not have any detrimental effect on sperm vitality, increases the percentage of spermatozoa displaying progressive motility and the percentage of acrosome-reacted spermatozoa. EVs produced and released in various regions of the female reproductive system likely contribute to spermatozoa maturation during their transit, promoting both capacitation and motility.